EDUKASI DAN PELATIHAN KELOMPOK MASYARAKAT TENTANG BANK SAMPAH - prayogi, bisepta; Risa Mariana, Evi; Pahruddin, Muhammad (UPPM Poltekkes Kemenkes Banjarmasin, 2023)
ABSTRACT Waste has always been a difficult problem for people who don't care about the environment. When people don't keep things clean, they can leave behind unpleasant piles of trash. According to the World Bank report